(untitled) (Journal of the Association for the Study of Australian Literature, 2013)
This paper provides an account of some of the more fanciful thinking about the new society England believed it was building in New South Wales with some comparative reflections on the French and British in New Holland. It refers to accounts by Governor Arthur Phillip, Captain John Hunter and others.